Primulina cordistigma, a new species of Gesneriaceae from Guangdong, China and supplementary and emendated description of floral morphology of P. yangchunensis - Lai, Bi-Dan; Wang, Bing-Mou; Wen, Fang (Phytotaxa, 2016)
Primulina cordistigma, a new species from Guangdong, China, is illustrated and described. This new species is similar to P. yangchunensis, from which it is distinguished by the leaf blades broadly ovate, 4–5 × 2–3.5 cm, base broadly cuneate to cordate, and margins entire or rarely undulate; the inflorescence a cyme 1–5-flowered; the bracts lanceolate, 3–4 × 0.5–1.0 mm; the corolla tube 0.9–1 cm long; staminodes 3; and the stigma cordate with elliptic lobes covered by shortly puberulent hairs. A conservation category of “Endangered” (EN) according to IUCN Red List Category and Criteria is proposed. Based on plenty of specimens with flowers and field works, the floral morphology of P. yangchunensis, which is the congener of P. cordistigma, is supplemented and emendated here.